Testing Radio Signal Range of Selected Components - Andrej Velas; Tomas Lovecek; Jan Valouch; Jacek Dworzecki; Eva Vnencakova (Communications - Scientific letters of the University of Zilina, 2018)
The radio signals range of selected wireless components of security systems is defined by the area within which components can communicate properly. In practice, the range of communication between components is often insufficiently taken into account, which results in the system malfunction. There are cases where the radio signal range of wireless components was inadequate due to use in an environment constructed from non-transmitting materials.The installation of wireless systems requires the implementation of a testing methodology of radio-communication range and its continuous improvement. Currently, the procedures within EN 50 131-5-3 and EN 300 220-1 standards can be used to test the wireless components, but they do not target the range between wireless components. Dependability and functionality are the main attributes of electrical security systems and need to be verified by testing the range of wireless components.